Membrane Damage Induced by Supercritical Carbon Dioxide in Rhodotorula mucilaginosa - Li, Jun (Springer-Verlag, 2013)
To clarify the mechanism of microbial inactivation by supercritical carbon dioxide (SCCO(2)), membrane damage of Rhodotorula mucilaginosa was investigated within specific pressure (10 Mpa), temperature (37 °C), and treatment time (10–70 min) ranges, including cell morphological structure, membrane permeability and fluidity. SEM and TEM observations showed morphological changes in the cell envelope and intracellular organization after SCCO(2) treatment. Increase of membrane permeability was measured as increased uptake of the trypan blue dye with microscopy, and leakage of intracellular substances such as UV-absorbing materials and ions by determining the change of protein and electrical conductivity. The SCCO(2) mediated reduction in CFU ml(−1) was 0.5–1 log higher at 37 °C and 10 MPa for 60 min in Rose Bengal Medium containing 4 % sodium than a similar treatment in Rose Bengal Medium. Membrane fluidity analyzed by fluorescence polarization method using 1,6-diphenyl-1,3,5-hexatriene showed that the florescence polarization and florescence anisotropy of the SCCO(2)-treated cells were increased slightly and gently compared with the untreated cells. The correlation between membrane damage and death of cells under SCCO(2) was clear, and the membrane damage was a key factor induced the inactivation of cells.